Community Acceptance Of Male Beauty Vloggers: A Study Of The Residents Of Padang Gading Village, Sungai Rumbai Subdistrict, Mukomuko Regency - Parwati, Nunuk; Narti, Sri; SM, Anis Endang (Social Sciences Journal, 2025)
This study aims to explore community acceptance of male beauty vloggers, focusing on the TikTok account @azkhategar391 in Padang Gading Village, Sungai Rumbai Subdistrict, Mukomuko Regency. The emergence of male beauty vloggers is often perceived as a challenge to traditional gender stereotypes, especially within rural communities that adhere strongly to conventional masculinity. The study employs a descriptive qualitative approach, utilizing data collection methods such as observation, in-depth interviews, and documentation. Informants were selected purposively based on criteria including age, residency, and activity on TikTok. The research is grounded in Stuart Hall’s encoding/decoding theory, which explains how media messages are produced (encoding) and how they are received or interpreted by audiences (decoding). The findings reveal diverse audience responses to male beauty vlogger content. Some participants fully accept the content (dominant-hegemonic reading), others respond with negotiation (negotiated reading), while a portion rejects it (oppositional reading). Factors influencing acceptance include age, educational background, religious values, and exposure to social media. The study highlights a shift in rural community perceptions of gender and beauty, though resistance to non-traditional gender expression remains. These findings are significant in understanding how digital media influences local social dynamics and the potential of social media to promote more inclusive views of gender roles.